A tetrasporic Octospora (Pyronemataceae, Pezizales) in South America - Suarez, Guillermo Martin (2025)
Octospora gemmicola var. tetraspora (Pyronemataceae), a species of bryophilous ascomycete, is recorded for the first time in South America from Argentina. This taxon is characterized by its parasitism on the propaguliferous moss Bryum klinggraeffii and the presence of tetrasporic asci. Macroscopic and microscopic features and ecological aspects of Octospora gemmicola var. tetraspora are discussed. Furthermore, pictures regarding conditions of the Argentinian occurrences, microscopic characters including spores, and infection structure are provided. Other related Octospora species with four-spored asci are discussed with the Argentinian collection, including a comparative illustration.